Gravitational Energy Levels: Part Two - Tannous, Edward (Journal of natural sciences, life and applied sciences, 2021)
We present here a model that explains in a simple, easy and summarized manner, the values, meaning and reasons for the force of gravity, using simple physical tools. According to this model, a gravitational field actually creates different energy levels, similar to the atom, around the center of mass of the gravitational source, and a transition between the energy levels results in the creation of the force of weight acting on each small body which is in the gravitational field. As the body approaches a gravitational field, its energy value decreases to a value of m0u2(R), proportional to the distance R between the centers of the masses, when u(R) is the magnitude of the self-speed of light vector (the progression in the time axis) of the small body, and its value decreases as it approaches the center of the origin of the field. This change in the energy levels is the cause of the force of gravity. A formula is obtained for the concept of potential gravitational energy and the variables on which it depends, and for the time differences between two frames that are in the gravitational field, taking into account the motion and location of each frame. It is obtained from this model that the speed of light is also a variable value as a result of the effect of the gravitational field.
Keywords: gravitational force; potential energy; kinetic energy; time differences between frames; photogravitational deviation